Expert consensus on unmanned aerial vehicle blood transportation in Shenzhen - Blood Transfusion Branch of Shenzhen Medical Association Expert Consensus Writing Group on Unmanned Aerial Vehicle Blood Transportation in Shenzhen (Zhongguo shuxue zazhi)
The unmanned aerial vehicle (UAV) blood transportation service is a convenient blood delivery way provided by the Shenzhen Blood Centre. It is also an essential part of the “Air-ground Integrated” blood delivery model. UAV blood delivery can avoid ground traffic or impassable road conditions, making blood transportation faster and more efficient, which is really important for urgent blood transfusions. The 5G+ UAV blood transportation intelligent platform achieves real-time high-definition video and cold chain temperature feedback throughout the entire process under the support of artificial intelligence and visual image analysis technologies. This UVA blood transportation system allows for visualized, manageable, controllable and traceable intelligent, integrated and open management, ensuring the quality and safety of cold chain blood transportation. Multiple medical institutions in Shenzhen have already implemented UAV blood delivery. However, there is currently a lack of safety standards for UAV blood transportation. To address this, the Blood Transfusion Branch of Shenzhen Medical Association has organized experts to discuss and formulate this consensus that aims to promote the standardized management of UAV blood delivery to better serve clinical patients.